Triptolide prevents extracellular matrix accumulation in experimental diabetic kidney disease by targeting microRNA‐137/Notch1 pathway. Issue 3 (13th September 2017) - Han, Fei; Wang, Shanshan; Chang, Yunpeng; Li, Chunjun; Yang, Juhong; Han, Zhe; Chang, Baocheng; Sun, Bei; Chen, Liming
Abstract : MicroRNAs (miRNAs) are involved in multiple biological functions via suppressing target genes. Triptolide is a monomeric compound isolated from a traditional Chinese herb, which exerts protective roles in many kinds of glomerular diseases. However, our understanding of the triptolide effect on miRNAome is still limited. In this study, we found that triptolide significantly decreased albuminuria and improved glomerulosclerosis in rats with diabetic kidney disease (DKD). And triptolide also inhibited extracellular matrix (ECM) protein accumulation and the notch1 pathway activation under diabetic conditions. MiR‐137 was significantly decreased in the HG (high glucose)‐treated HRMCs and in the kidney tissues of the diabetic rats, but was upregulated by triptolide. In addition, overexpression of miR‐137 exerted similar effects to those of triptolide, while miR‐137 inhibition aggravated ECM protein accumulation. Luciferase reporter assay results demonstrated that miR‐137 directly targets Notch1. Furthermore, the miR‐137‐dependent effects were due to Notch1 suppression that in turn inhibited ECM protein expression, key mediators of glomerulosclerosis. Finally, downregulation of miR‐137 reversed the ECM inhibition role of triptolide in HG cultured HRMCs. Taken together, these findings indicate that triptolide is a potential therapeutic option for DKD and that miR‐137/Notch1 pathway play roles in the anti‐glomerulosclerosis mechanism of triptolide. Abstract : Diabetic condition decreases the miR‐137 levels in renal mesangial cells. MiR‐137 decreases the expression of Col IV and FN by targeting Notch1. On the other hand, triptolide may protect DKD against glomerulosclerosis by targeting miR‐137/Notch1 pathway.